Extraction of bioactive compounds from curry leaves (Murraya koenigii) using solvent extraction method: article - Dzulkifli, Nurul Syahirah; Ismail, Norhuda (2017)
Murraya koenigii also known as curry leaves are used as a flavour ingredient and has a lot of bioactive components which can be found inside the plant. The amount of people in Malaysia that are still not aware of curry leaves medicinal values due to lack of exposure is quite alarming. This research objective are to extract essential oils from Murraya koenigii by using solvent extraction method, to determine the highest oil content in Murraya koenigii by using three different solvent which are pure methanol, pure ethanol and distilled water, to identify bioactives content in Murraya koenigii using GC-MS to determine chemical structure in Murraya koenigii using FTIR. The result shows that Methanol solvent yield the highest oil content. The functional group was also identified where it was classified as O-H, C-H bond, Benzene and Esters group. Bioactive compounds of the essential oil performed by using GC-MS detected the presence of α-Pinene, α-Caryophyllene, α-Terpineol and Estragole. All four has potential medical benefits to human which α-Pinene exhibits anti-inflammatory and anti-microbial properties while α-Caryophyllene has anticarcinogenic properties, α-Terpineol reduces mechanical hypernociception and inflammatory response and Estragole gives local anesthetic activity. Since the bioactives compound are sucessfully found in Murraya koenigii leaves, it is hoped that Malaysians will be much aware with the health benefits of Murraya koenigii and will start to consume it instead of throwing it away.